The Conceptualization of Genre in Systemic Functional Linguistics - Hesham Suleiman Alyousef; Asma Mohammed Alyahya (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2018)
Genre constitutes the rhetorical features of a text and the semiotic communicative purpose(s) it serves. It has marveled Systemic Functional Linguisticsâ€™ (SFL) scholars as to whether it should be treated as an aspect of the situational context (register) or as a distinct cultural semiotic system that correlates with texture- i.e. the three register categories of field, tenor, and mode. This paper aims to review the conceptualization of genre in the Systemic Functional Linguistics (SFL) tradition. Whereas Halliday associates genre with mode, Martin coordinates the three register variables of field, tenor, and mode in relation to social purpose. The elements of a schematic structure are generated by genre networks, which in turn preselect particular values of field, tenor and mode in a given culture. Both Halliday's context of situation and Martinâ€™s context of culture levels are dynamic connotative semiotic systems through which new meanings are created by the three processes of semogenesis. Genre is conceived as a distinct cultural semiotic system, rather than an aspect of â€˜modeâ€™, that correlates with texture. Martin later avoided the intertextual glosses context of culture and context of situation since Halliday used them for instantiation, and not supervenience. The three register variables of language organize information at the level of genre into coherent texts. Modelled as register and genre, the stratified model of context configures meanings not only through discourse semantics, lexicogrammar, and phonology but also through the prosodic phases of evaluation. Halliday calls this model appliable linguistics since it enables us to develop a powerful model of language that is both â€œtheoreticalâ€ and â€œappliedâ€ (Mahboob & Knight, 2010).